The efficiency of incorporation of the drama technqiues into the teaching of English literature among form three stduents in SMK TTDI Jaya / Nurul Diyanah Khalid - Khalid, Nurul Diyanah (Faculty of Education, 2014)
The study aims to investigate the efficiency of the incorporation of drama techniques into the teaching of English literature. This study has several purposes which are to identify the differences between drama techniques and the ones being used by teachers, advantages and disadvantages of using drama techniques into the teaching of English literature as well as the efficiency of the incorporation. This research was done using mixed approach where questionnaires were used to gather data from the respondents. The samples of the study consist of 40 students from Form 3 Nano and Form 3 Alpha of Sekolah Menengah Kebangsaan TTDI Jaya, Selangor. The findings show that the students have been exposed to various drama techniques when teaching English literature.However, not all techniques have been used in class due to practicality and other conditions. Despite being used in classes, there are advantages and disadvantages of the incorporation which the teachers and students need to consider. On the basis of the results of this research, it can be concluded that the incorporation of drama techniques when teaching English literature is efficient and has helped the students learn English literature better.